Model-Model Pengembangan Atraksi Wisata Wonosobo - Agus Maladi Irianto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Wonosobo is known as a mountainous area that stores the assets of nature tourism. The advantages of natural attractions, ideally should be supported by local communities. Tourist attractions are traditional art performances of local communities that support these needs. As an integrative need, the traditional art of the Wonosobo people - most of whom are farmers in the agricultural world - will be preserved as long as it is able to accommodate their views, aspirations, and ideas. Tourism development will work well, if supported by the views, aspirations, and ideas of local communities. From here it is necessary to find models of the development of traditional art attractions in the region Wonosobo. The purpose of this study is broadly directed to two things. Firstly, it provides new insight into the strategy and development of natural tourism that is in line with the local art assets, both regarding management system and the awareness of the potential of the area. Second, implement participatory approach models for local communities in order to formulate regional development policies, in particular the development of tourist areas